R-E-S-P-E-C-T: The Relationship Between Being Respected and Quality of Life of Disabled People - Friedman, Carli (Disability Studies Quarterly, 2018)
The United Nations exclaims "all human beings have the right to be treated with dignity and respect" (Annan, 2005, p. 34). Yet, disabled people have long been denied respect in the United States and have been subjected to disability oppression and ableism. For these reasons, the aim of this study was to explore the relationship between respect and disability, particularly respect's impact on the quality of life of disabled people. We had two research questions: (1.) what factors predict disabled people being respected? and, (2.) how does being respected impact the quality of life of disabled people? To explore these questions, we used secondary Personal Outcome Measures® data from approximately 1,500 disabled people; we analyzed this data to examine relationships between disabled people's interpretations of feeling and being respected, and their quality of life. Our findings revealed being respected had a significant impact on every area of ones' quality of life. Problematically, this also included areas which should be considered non-negotiable fundamental human and civil rights, that should not depend on if, and how, people respect disabled people. While the attitudes underlying the disrespect of disabled people are harmful and problematic, human and civil rights should be inalienable – ones' access to exercise their rights, to safety, to health, and to many other domains should not depend on others' attitudes about, and treatment toward, you.